2006
DOI: 10.1007/s10464-006-9069-9
|View full text |Cite
|
Sign up to set email alerts
|

Being Silenced: The Impact of Negative Social Reactions on the Disclosure of Rape

Abstract: Rape survivors who speak out about their assault experiences are often punished for doing so when they are subjected to negative reactions from support providers. These negative reactions may thereby serve a silencing function, leading some rape survivors to stop talking about their experiences to anyone at all. The current study sought to examine this worst case scenario. Focusing on the qualitative narratives of eight rape survivors who initially disclosed the assault but then stopped disclosing for a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
350
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(373 citation statements)
references
References 36 publications
15
350
1
7
Order By: Relevance
“…These findings are consistent with previous studies in Jordan, which identified the most prevalent forms of abuse against women as physical abuse, forceful marriage, lack of access to education and right to inheritance, sexual harassment and unfair laws [6,7]. Abuse, regardless of its form, endangers the quality of life and health and reduces the productivity of women by suppressing their ability to express and participate as effective members of society [17]. The psychological and social consequences of abuse are multifaceted.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with previous studies in Jordan, which identified the most prevalent forms of abuse against women as physical abuse, forceful marriage, lack of access to education and right to inheritance, sexual harassment and unfair laws [6,7]. Abuse, regardless of its form, endangers the quality of life and health and reduces the productivity of women by suppressing their ability to express and participate as effective members of society [17]. The psychological and social consequences of abuse are multifaceted.…”
Section: Discussionsupporting
confidence: 91%
“…Having clear standards of membership allows for the "othering" of the individual making the allegations against the institution, as nonconforming attributes of individuals can be highlighted in order to cast doubt on the veracity or importance of reports (Herman, 1998). It can serve to create an "us versus them" mentality common in group cohesion (Bloom & Farragher, 2010) and may represent an additional level of betrayal when divided loyalty within an organization leads to further isolation (Ahrens, 2006). For example, women who report military sexual trauma are often questioned about their sexual history and substance use by military authorities (Campbell & Raja, 2005).…”
Section: Institutional Denialmentioning
confidence: 99%
“…Rape disclosure receipt is a relatively common phenomenon, with approximately 20-40% of college students (Banyard, Moynihan, Walsh, Cohn, & Ward, 2010; and 35% of women in a national sample (Paul et al, 2014) reporting this experience. Despite the support and services that disclosure may yield for to victims (e.g., Ahrens et al, 2007;Ullman, 2010;Ullman & Filipas, 2001), it is well-documented that negative reactions to disclosure lead to greater victim self-blame (Ullman, 1996), adverse mental health outcomes (Davis, Brickman, & Baker, 1991;Ullman & Filipas, 2001), and a decreased likelihood of reporting the assault to police (Ahrens, 2006). If the label given to an act of sexual violence by the victim or the disclosure recipient leads to a negative reaction (e.g., minimized severity of the assault), or if such a response is engendered by inconsistencies between the label assigned by the victim and how it is interpreted by the recipient, victim outcomes may be adversely affected.…”
Section: Labeling Sexual Violencementioning
confidence: 99%